Barriers to Utilization of Intermittent Preventive Treatment with Sulfadoxine Pyrimethamine in Pregnancy at Private Facilities in Tema Metropolis - Amankwah, S. (University of Ghana, 2017)
Background: The National Malaria Control Program of Ghana recommends the use of intermittent preventive treatment of malaria in pregnancy using sulfadoxine pyrimethamine (SP) to prevent malaria and associated complications. There is overwhelming evidence, however, that uptake of this intervention in the country is low. This low uptake is more prominent in private health facilities. Objective: This study examined factors associated with low uptake of three or more doses of SP among pregnant women who received antenatal care (ANC) services at selected private hospitals in the Tema metropolis. Methods: A cross-sectional descriptive study was carried out among ANC attendants and midwives using the mixed method approach. ANC attendants were consecutively recruited into the study at the selected private hospitals as they came for ANC. Respondents demographic characteristics, knowledge on intermittent preventive treatment (IPTp)-SP, implementation of directly observed therapy (DOT), experience of drug side effects, liming of first ANC visits and total number of ANC visits made during the period of pregnancy were assessed. Supply of logistics, documentation of SP, reporting of SP uptake, and monitoring and evaluation of lPTp-SP were also assessed. In-depth interviews involving midwives in charge of the facilities were also conducted. Audio recordings of the interview were transcribed and manually analyzed. Chi-square test was done to assess socio-demographic differences in SP uptake. Both bivariate and multiple logistic regression were used to generate crude odds ratio and adjusted odds ratios. Odds ratios were estimated to assess the strength of the associations using a 95% confidence intervals for significance testing. The level of significance was Results: Out of the 384 respondents, 179(46.6%) had taken 3 or more doses by their last month of pregnancy. Out of the 177 respondent who reported to ANC in their first trimester. 98/177 (54.8%) had taken at least 3 doses of SP. whilst 77/183(43.3%) of the respondents who reported in the second trimester had taken at least 3 doses.Twenty four reported in their third trimester with only 4/24 (2.2%) of them taking at least 3 doses. Majority of the respondents (234/384) had information given to them by midwives prior to administration. Out of this, 71.2% took three or more doses. Also, 50/192 (72.1%) of respondents who attended ANC more than five times had received at least three doses. Qualitative analysis showed poor adherence to DOT, low knowledge of midwives on IPTp-SP and active support of program implementers on IPTp-SP as an intervention. CONCLUSION: The proportion of uptake of at least three doses of SP is low and not encouraging since the NMCP has a target of 55% for uptake of 3 or more doses. Increased number of ANC visits, timing of first ANC visit and prior information given on SP by midwives had a significant relationship with uptake of SP. Knowledge of midwives on IPTp-SP was low, midwives could not mention WHO guidelines on SP administration. Support from program implementers was adequate but monitoring and evaluation was not frequently done on SP. Private ANC workers did not adhere to DOT in SP administration.
MSc. Public Health
Keywords: Intermittent Preventive Treatment; Sulfadoxine Pyrimethamine; Pregnancy; Private Facilities; Tema Metropolis; Ghana